ANALYSIS OF FACTORS AFFECTING EARNINGS MANAGEMENT WITH PROFITABILITY AS MODERATING VARIABLES ON MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Siahaan, Nenni Kristina (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to analyze the factors that influence earnings management with profitability as a moderating variable. The factors analyzed were information asymmetry, leverage,firm size, institutional ownership , and managerial ownership. This type of research is causal associative. The study population was 50 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2015. The sampling method is a census, so the number of samples used is 200 observation data . Hypothesis testing is done using multiple linear regression analysis and residual test. The results showed partially information asymmetry, institutional ownership and managerial ownership had a positive and significant effect on earnings management, while the leverageand size of the company had a positive and not significant effect on earnings management. Simultaneously information asymmetry, leverage,firm size, institutional ownership and managerial ownership have a significant effect on earnings management. Profitability as a moderating variable cannot moderate the relationship between information asymmetry, leverage, firm size, institutional ownership and managerial ownership with earnings management.